COMPARATIVE ANALYSIS ON TECHNICAL EFFICIENCY OF VEGETABLE PRODUCTION UNDER TWO FARMING SYSTEM IN IMO STATE, NIGERIA - Ogunmola, Omotoso (Journal of Agricultural Sciences (Belgrade), 2021)
Increasing agricultural productivity via versatile production systems is critical for sustainable food security and economic development. The study aims at comparing the technical efficiency of vegetable production and factors influencing the technical efficiency of vegetable production between inorganic and organic farming system in Imo state, Nigeria.  Primary data were collected using structured questionnaires from 100 vegetable farmers using multistage sampling techniques. Budgetary analysis and stochastic production frontier model were used to estimate the profitability and the technical efficiencies of the enterprise respectively. The results revealed that both organic and inorganic vegetable production is profitable; however, the inorganic farming system had significantly higher returns than organic farming system. The mean technical efficiency organic vegetable farmers were 89.57% and 75.64% for inorganic farmers. Farm size, labour and quantity of seeds used were the crucial factors that contributed to the technical efficiency under both farming system. More so, age, years of education and farming experience are the significant variables that influence technical inefficiency of inorganic farmers while years of education and household size significantly influence technical inefficiency of organic farmers. This study advocates for premium prices to be given to the organic farmers to compensate their lower yield and policies that would attract young people into vegetable farming to increase the level production.
Keywords: comparative analysis, stochastic frontier, technical efficiency, vegetable production